Enhancing Lae-Lae Island sustainability: computer vision based waste detection and analysis - Nasir, Arnold; Syariati, Kasmir; Suardi, Citra; Sundoro, David; Lordianto, Reinaldo Lewis (Association for Scientific Computing Electrical and Engineering, 2024)
In our study,